Tissue Engineering and Regenerative Medicine: Achievements, Future, and Sustainability in Asia - Han, Fengxuan; Wang, Jiayuan; Ding, Luguang; Hu, Yuanbin; Li, Wenquan; Yuan, Zhangqin; Guo, Qianping; Zhu, Caihong; Yu, Li; Wang, Huan; Zhao, Zhongliang; Jia, Luanluan; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Exploring innovative solutions to improve the healthcare of aging and diseased population continues being a global challenge. Among a number of strategies toward this goal, tissue engineering and regenerative medicine (TERM) has gradually evolved into a promising approach to meet future needs of patients. TERM has recently received increasing attention in Asia, as evidenced by the markedly increased number of researchers, publications, clinical trials and translational products. This review aims to give a brief overview of TERM development in Asia over last decade by highlighting some of the important advances in this field and featuring major achievements of representative research groups. The development of novel biomaterials and enabling technologies, identification of new cell sources, and applications of TERM in various tissues are briefly introduced. Finally, the achievement of TERM in Asia, including important publications, representative discoveries, clinical trials and examples of commercial products will be introduced. Discussion on current limitations and future directions in this hot field will also be provided.